Effects of shading and blocking in compact linear fresnel reflector field. (1st January 2016) - Sharma, Vashi; Khanna, Sourav; Nayak, Jayanta K.; Kedare, Shireesh B.
Abstract: In a compact linear fresnel reflector field, 's' number of reflector-rows lying between two receivers can be configured in 2 s ways. Each possible configuration will lead to different energy loss, electricity generation and cost of electricity. The variations in energy losses, energy collection by fluid, electricity generation and cost of electricity with length (L) and width (w) of aperture of a reflector-row, spacing between adjacent reflector-rows (p), number of reflector-rows (2n), receiver-height (H), collector-configuration and location have been studied. It is found that the collector configuration has no significant effect on annual shading. However, it affects annual energy losses due to cosine effect, blocking and the factors τ and α significantly. As a result, the cost of electricity can be improved significantly by varying collector configuration. The cost of electricity decreases with increment in p/w and later on, it starts increasing. The best p/w ratio corresponding to minimum cost of electricity is 1.44 for H/nw = 0.3 and 1.85 for H/nw = 0.7. The energy collection by fluid increases rapidly with increment in H/nw initially. However, beyond H/nw about 0.7, further increase in H/nw does not lead to significant increase in energy collection. Highlights: Cost of electricity is found out incorporating shading and blocking. Effects of spacing, receiver height and collector configuration are investigated. Annual shading does not depend much on collector configuration. Annual blocking can be reduced significantly using appropriate configuration. Configuration resulting minimum blocking also yields minimum cost of electricity.